Accommodation of L2 Speech in a Repetition Task: Exploring Paralinguistic Imitation - Burin, Léa (Research in Language, 2018)
Phonetic convergence is the process by which a speaker adapts his/her speech to sound more similar to his/her interlocutor. While most studies analysing this process have been conducted amongst speakers sharing the same language or variety, this experiment focuses on imitation between non-native and native speakers in a repetition task. The data is a fragment from the ANGLISH corpus designed by Anne Tortel (Tortel, 2008). 40 French speakers (10 male intermediate, 10 male advanced, 10 female intermediate and 10 female advanced learners) were asked to repeat a set of 20 sentences produced by British native speakers. Segmental (vowel quality), suprasegmental (vowel duration) and voice quality were analysed. Level of proficiency, gender and model talker were taken as independent variables. Level appeared not to be a relevant parameter due to a high amount of inter-individual variability amongst groups. Somewhat contradictory results were observed for vowel duration and F1-F2 distance for male learners converged more than female learners. Our hypothesis that low vowels display a higher degree of imitation, and especially within the F1 dimension (Babel, 2012), was partially validated. Convergence in vowel duration in order to sound more native-like was also observed (Zając, 2013). Regarding the analysis of voice quality, and more particularly of creaky voice, observations suggest that some advanced female learners creaked more than the native speakers and more in the reading task, which indicate, both linguistic idiosyncrasy and accommodation towards the native speakers. Low vowels seem also to be more likely to be produced with a creaky voice, especially at the end of prosodic constituents.